Investigating the digital health acceptance of Korean baby boomers: Comparative study of telemedicine and wearable healthcare devices. Issue 1 (March 2023) - Kim, Eunhye; Han, Semi
Highlights: We compared factors influencing telemedicine and wearable healthcare device acceptance. This study targets baby boomers, who can be the biggest beneficiary of digital health. Multidisciplinary theories were applied by reflecting the convergence characteristics. The practical implications of how digital health services approach targets were presented. Abstract: Objective: In the COVID-19 era, the importance of and need for digital health services, such as telemedicine and wearable healthcare devices, are increasing. Although these services are treasured by older adults, their acceptance rates remain low. Thus, we attempted to find ways to enhance the acceptance rates of these services by investigating factors that influence the digital health acceptance of baby boomers. Based on the behavioral model of health service use and a multi-dimensional value perspective, we developed a research model to compare the factors influencing telemedicine and wearable healthcare device acceptance. Methods: To examine the research model, we conducted face-to-face surveys with 300 baby boomers. The survey consisted of two sections: telemedicine and wearable healthcare devices. We used measurement instruments that had been validated in previous studies. Results: Each research model's measurement model and structural model were evaluated. The reliability and validity of the measurement items of each model were satisfactory. The structural model test illustrates that three beliefs (usefulness, information, and cost saving) are important for the acceptance of telemedicine and wearable healthcare devices. Reassurance and convenience only significantly influence telemedicine and wearable healthcare devices, respectively. Among need and enabling factors, subjective health and income affect the intention to accept telemedicine and wearable healthcare devices. Conclusions: This study has theoretical implications in that it applied multidisciplinary theories by reflecting on the convergence characteristics of digital health, which are health and digital. In addition, it provides managerial implications to promote baby boomers' acceptance of digital health services.